Storytelling for leaders tales of sorrow and love - Kets de Vries, Manfred F. R. (Routledge, 2025)
"Stories matter. Written by renowned psychoanalyst, leadership scholar, and executive coach, Manfred Kets de Vries, this book uncovers, explains and captures the power and art of storytelling at work and in life, and how it can be applied in organizations to powerful effect. Our talent in telling stories makes us more effective. When we talk about events, characters, actions, themes, feelings, and ideas, storytelling is a way to communicate our message. The stories we tell inform, influence, entertain, and shape our lives and those of other people. Using an engaging and storytelling style throughout, the book explores the important role of storytelling, with a particular focus on how it is one of the most important ways to develop leadership skills. Not only does this book present a clear method for improving our storytelling skills, it also explores themes such as the tendency of some people not to live up to their full potential, why people assume an attitude of helplessness, the effects of adversity on human development, why people behave stupidly, the psychological dynamics which affect influencers, the role of sexuality in career management, and what needs to be done to have a fulfilling life. The book is perfect for organizational leaders looking to develop their understanding and skills in the art of storytelling, thereby increasing their effectiveness in positive and powerful ways"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Leadership; Storytelling; Communication in management; Art de conter; Communication en gestion; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Consulting